The Effectiveness of Guided Inquiry Based E-LKPD to Improve Metacognitive Skills on Reaction Rate Material - Ardani, Selfi Novia; Utiya Azizah (PendIPA Journal of Science Education, 2026)
Students' metacognitive skills on reaction rate material are still low, so it is necessary to innovate digital-based teaching materials that can facilitate the process of planning, monitoring, and evaluating learning. This study aims to evaluate how well guided inquiry-oriented e-LKPD improves students' metacognitive skills on reaction rate material. Students of SMA Negeri 1 Slahung were used as research subjects. This study used a one-group pretest-posttest design and was pre-experimental. The results of the pretest and posttest of metacognitive skills were used to collect research data. The method used for data analysis was the Paired Sample t-Test. The results of the Paired Sample t-Test showed a significance value of 0.000 (<0.05). Therefore, it can be said that guided inquiry-based e-LKPD successfully improved students' metacognitive skills on reaction rate material.